Community Structure of Bivalves in The Mangrove Ecosystem in The Teluk Buo, Bungus Sub-district,Teluk Kabung District, Padang, Sumatera Barat Province - Silvi Rahmi; Adriman '; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Teluk Buo mangrove forest is one of tourist destination in the Sumatera BaratProvince. The input of pollutant originated from anthropogenic activities, however,reducing the water quality and as a consequence negatively affects the mangroveecosystem as well as the associated organisms, including bivalves. To understand thecommunity structure of bivalves in the mangrove ecosystem, a research wasconducted on February 2017. The observation of bivalve community is done bymaking line transects. There were 3 transect lines and in each line, 9 sub plots (1x1m)observed. The bivalves present in the plots were collected manually everyday for 2weeks period. Results shown that there were 6 bivalves species present, they wereGeloina erosa, Anadara antiquata, Barbatia sp., Lucinoma galathea, Chameleastriatula and Trychardium sp. with bivalves abundance was ranged from 6,667 to31,481 organisms/ha. The value of diversity index (H’) was 0.2650-2.403, thedominance index (C) was 0.210-0.722 and the uniformity Index (E) was 0.059-0.563.The bivalva community structure in Teluk Buo is moderate with the dominant species(Geloina erosa) has been disturbed by the existence of ecological pressure and thedominant species causing unbalanced mangrove area. Abiotic environmental factorsinclude temperature was 29-31 0C; pH of water was 7.3-7.5, soil pH 7.1-7.2 andsalinity was 25-340/00.Key words: Bivalves, Mangrove Ecosystem, Teluk Buo, Water Quality